« Tu n'as pas l'air autochtone! »: et autres préjugés - Larivière, Widia; Lumsden, Mélanie; Ottawa, Meky (Amnistie internationale, 2021)
« Les préjugés négatifs à l'encontre des autochtones existent et sont ancrés depuis longtemps dans la mémoire collective. Consciemment ou non, beaucoup croient encore que les autochtones sont trop revendicateurs, dépendants, profiteurs ou vivant de l’aide sociale, par exemple. Ce livret démystifie dix préjugés parmi les plus souvent entendus autour des autochtones. »-- Amnistie.ca.
Keywords: amériques; approches et analyses; canada; communication; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; pédagogie; racisme; régions géographiques; sciences de l'éducation; sex2283; système colonial; systèmes d'oppressions; thématiques; violences

Decolonizing methodologies: research and indigenous peoples - Smith, Linda Tuhiwai (Zed Books, 2021)
''To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory.This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being.Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry.''-- Site de l'éditeur.
Keywords: approches et analyses; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; militance; méthodologie; méthodologie autochtone; pol4105; premier cycle; pédagogie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; études autochtones

Land as pedagogy: Nishnaabeg intelligence and rebellious transformation - Simpson, Leanne Betasamosake (Decolonization: Indigeneity, Education & Society, 2014)
A resurgence of Indigenous political cultures, governances and nation-building requires generations of Indigenous peoples to grow up intimately and strongly connected to our homelands, immersed in our languages and spiritualities, and embodying our traditions of agency, leadership, decision-making and diplomacy. This requires a radical break from state education systems – systems that are primarily designed to produce communities of individuals willing to uphold settler colonialism. This paper uses Nishnaabeg stories to advocate for a reclamation of land as pedagogy, both as process and context for Nishnaabeg intelligence, in order to nurture a generation of Indigenous peoples that have the skills, knowledge and values to rebuild our nation according to the word views and values of Nishnaabeg culture.
Keywords: amériques; approches et analyses; canada; cours; discipline; environnement; féminisme autochtone; histoire et politique; nishnaabeg; pol4105; premier cycle; premières nations; pédagogie; pédagogie nishnaabeg; régions géographiques; résistance; résurgence; savoirs autochtones; sciences de l'éducation; sciences humaines; sociologie; système colonial; systèmes d'oppressions; systèmes éducatifs; territoire nishnaabeg; thématiques; éducation par le territoire

Anishnaabe-Kwe, traditional knowledge, and water protection - McGregor, Deborah (Canadian Woman Studies, 2008)
26CANADIAN WOMAN STUDIES/LES CAHIERS DE LA FEMMEDans cet article, l’auteure partage ses expériences de travail sur les questions environnementales, particulièrement sur celles qui concernent l’eau. Comme mère, comme membre d’un clan, comme membre des Premières Nations et comme professeure, l’auteure se sent responsable du partage de ses connaissances. Cette réflexion est basée sur son travail avec les aînées et les tenants du savoir traditionnel en Ontario, surtout de celui qui se rapporte à l’eau. L’information part de deux projets majeurs dans lesquels elle a été impliquée.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droit; droit de l'environnement; eau; environnement; féminisme autochtone; ontario; point de vue situé; pol4105; premier cycle; pédagogie; périodes historiques; régions géographiques; science politique et droit; sciences de l'éducation; thématiques; transmissions; écoféminisme; écoféminisme amérindien

Itinéraires d'égalités. Trajectoires des femmes autochtones du Québec et du Canada - Levesque, Carole; Labrecque, Marie France (30e anniversaire de l’Association des Femmes Autochtones du Québec, 2007)
À l’occasion du 30e anniversaire de l’Association des Femmes autochtones du Québec, ces actes de colloque proposent de revoir le parcours des femmes autochtones dans leurs luttes pour l’égalité et la justice sociale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; environnement; féminisme autochtone; histoire et politique; inégalités; justice sociale; mexique; militance; pol4105; premier cycle; pédagogie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones